Text, image, and otherness in children's Bibles what is in the picture? - Vander Stichele, Caroline; Pyper, Hugh S. (Atlanta : Society of Biblical Literature, 2012)
"Children's Bibles are often the first encounter people have with the Bible, shaping their perceptions of its stories and characters at an early age. The material under discussion in this book not only includes traditional children's Bibles but also more recent phenomena such as manga Bibles and animated films for children. The book highlights the complex and even tense relationship between text and image in these Bibles, which is discussed from different angles in the essays. Their shared focus is on the representation of 'others' foreigners, enemies, women, even children themselves in predominantly Hebrew Bible stories. The contributors are Tim Beal, Ruth B. Bottigheimer, Melody Briggs, Rubn R. Dupertuis, Emma England, J. Cheryl Exum, Danna Nolan Fewell, David M. Gunn, Laurel Koepf, Archie Chi Chung Lee, Jeremy Punt, Hugh S. Pyper, Cynthia M. Rogers, Mark Roncace, Susanne Scholz, Jaqueline S. du Toit, and Caroline Vander Stichele" -- Publisher description.
pt. 1. Identifying the strange other. -- Inside out: the othered child in the Bible for children / Laurel Koepf -- "All God's children": authority figures, places of learning, and society as the other in creationist children's Bibles / Jaqueline S. du Toit -- Looking into the lions' den: otherness, ideology, and illustration in children's versions of Daniel 6 / Hugh S. Pyper -- The other in South African children's Bibles: politics and (biblical) systems of othering / Jeremy Punt -- Veggies, women, and other strangers in children's Bible DVDs: toward the creation of feminist Bible films / Susanne Scholz -- pt. 2. Learning how to deal with the other. -- No greater love: Jonathan and his friendship with David in text, tradition, and contemporary children's literature / Cynthia M. Rogers and Danna Nolan Fewell -- The word became visual text: the boy Jesus in children's Bibles / Melody Briggs -- Depiction of the devil and the education of Chinese children: the Bible in the Taiping Trimetrical classic / Archie Chi Chung Lee -- Conflating creation, combining Christmas, and ostracizing the other / Mark Roncace -- pt. 3. Destroying the other. -- "The water's round my shoulders, and I'm--GLUG! GLUG! GLUG!": God's destruction of humanity in the flood story for children / Emma England -- Samson's suicide and the death of three thousand others in children's Bible stories through two centuries / David M. Gunn -- Translating the Bible into pictures / Rubén R. Dupertuis -- Samson's hair and Delilah's despair: reanimating Judges 16 for children / Caroline Vander Stichele -- Responses. -- Children's Bibles hot and cold / Timothy Beal -- The otherness of children's Bibles in historical perspective / Ruth B. Bottigheimer -- What does a child want?: reflections on children's Bible stories / J. Cheryl Exum.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Bible -- Criticism, Narrative; Strangers in the Bible; Bible -- Language, style; Bible -- Criticism, interpretation, etc; Imagery (Psychology) in children; Imagination -- Religious aspects; RELIGION / Biblical Studies / History & Culture; Electronic books